2010
DOI: 10.1007/s10800-010-0130-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited Zn–TiO2 nanocomposite coatings and their corrosion behavior

Abstract: The present paper aims to investigate the electrodeposition on steel substrate and the corrosion behavior of Zn-TiO 2 nanocomposite coatings. Zn-TiO 2 composite coatings were electrodeposited on OL 37 steel from an electrolyte containing ZnCl 2 , KCl, HBO 3 (pH 5.7) brightening agents and dispersed nanosized TiO 2 . Corrosion measurements were performed in 0.2 g L -1 (NH 4 ) 2 SO 4 solution (pH 3) by using electrochemical methods (open-circuit potential measurements, polarization curves, electrochemical impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 26 publications
2
41
0
4
Order By: Relevance
“…The higher R P value was due to both charge transfer resistance and increase in the thickness of the corrosion product layer. The decrease in double layer capacitance resulted from a reduction in the local dielectric constant and/or from increased double layer thickness (Vlasa et al 2010).…”
Section: Corrosion Studiesmentioning
confidence: 99%
“…The higher R P value was due to both charge transfer resistance and increase in the thickness of the corrosion product layer. The decrease in double layer capacitance resulted from a reduction in the local dielectric constant and/or from increased double layer thickness (Vlasa et al 2010).…”
Section: Corrosion Studiesmentioning
confidence: 99%
“…After 24 h of immersion time, the corrosion resistance of the plated sample continuously decreases, as shown in Figure 14. Feng et al, [44,45] Gomes et al, [46] and Vlasa et al [53] have reported similar results.…”
Section: Impedance Spectroscopy Analysismentioning
confidence: 61%
“…Presently, a strong emphasis on the development of advanced functional and smart coatings for corrosion protection in different technological applications is observable [3]. One approach to increase wear and corrosion protection of conventional applications is the incorporation of hard particles in zinc coatings by electrodeposition with hexavalent chromium free passivation layers [4][5][6][7], which would reduce problems related to crack and hole formation in such coatings. However, in electrolytes submicron particles tend to significantly agglomerate due to strong electrostatic particle-particle interactions as a result of the high electrical conductivity of electrolytes.…”
Section: Introductionmentioning
confidence: 99%